Konsentrasi Fenolik Total dan Aktivitas Antioksidan dari Ekstrak Metanol Daun Kari (Murraya koenigii L.): Hasil Penelitian - Tanuhariono, Ardhita Felicia; Limanan, David; Ferdinal, Frans; Yulianti, Eny (Cermin Dunia Kedokteran, 2025)
Introduction: Curry leaves (Murraya koenigii L.) are plants that naturally grow in the Indian subcontinent, except at the peak of the Himalayan mountains, which in their development have spread widely to various corners of the world. Traditionally, curry leaves have been used by people as medicine. However, it is now known that this plant contains carbazole alkaloid compounds and polyphenols that have antioxidant activity. This is very useful for controlling free radical levels in the human body so that they remain within reasonable limits. This is very useful for controlling the levels of free radicals in the human body to stay within reasonable limits. Free radicals are produced by normal cell metabolism which has recently been associated with the pathophysiology of various diseases. Methods: This in vitro research was to determine phenolic content and antioxidant potential in methanol extract of curry leaves. Total phenolic content testing used the Folin-Ciocalteu method and expressed by Gallic Acid Equivalent (GAE). Total antioxidant capacity testing used the DPPH method and Trolox as a comparison solution. Results: The total antioxidant capacity is expressed in the form of IC50. The total phenolic content of curry leaf methanol extract was 4007.78 μg/mL or equivalent to 133.59 mg GAE/g DW and the total antioxidant capacity of curry leaf methanol extract was 37.418 μg/mL. Conclusion: The total phenolic content of curry leaf methanol extract is high (>5 mg GAE/g). Correspondingly, the total antioxidant capacity of curry leaf methanol extract is also classified as very strong (<150 µg/mL).